Book Review of Kaandossiwin: How We Come to Know - Steffie Dmello (Canadian Journal for New Scholars in Education)
Book Review of Kaandossiwin: How We Come to Know. Dmello reviews Kathleen E. Absolon’s influential work on Indigenous research methodologies, highlighting the Petal flower framework as a holistic model rooted in Indigenous epistemologies. The review discusses how Absolon centers land, spirit, relationality, and oral knowledge, challenging the dominance of Western paradigms in academia. Dmello emphasizes the book’s value for both Indigenous and non-Indigenous scholars, particularly in fostering reflexivity, decolonial ethics, and respect for oral traditions in research.